MacEwan's student work deposit form - Hall, Robyn (My University, 2022)
Brief overview of MacEwan University's institutional repository student deposit form workflow, and future directions for this service.
Presented February 8, 2022 at the CARL Repository Workflows Community Call held virtually.
Keywords: institutional repositories; undergraduate research